(untitled) (Gestão & Regionalidade, 2025)
The literature shows that 4.0 technologies have a significant impact on facing the housing deficit and sustainability. However, in the civil construction sector, there are social and technical implications that make this transformation difficult, especially for companies located in emerging countries. Thus, understanding managers’ perceptions can help in formulating strategies and public policy. We study the challenges and opportunities of new technologies according to the managers’ perception of construction companies located in Pernambuco, Brazil. The results demonstrate that the lack of interest of managers, lack of capital, and lack of Knowledge are recognized barriers to implementing 4.0 technologies in the construction sector. Although managers know that 4.0 technologies can contribute to reducing costs, and increasing productivity, quality, and competitiveness, most of them have difficulties relating the current organizational culture with the challenges of adopting new technologies.